Kant : political writings - Kant, Immanuel, 1724-1804; Reiss, Hans Siegbert; Nisbet, H. B. (Hugh Barr) (Cambridge : Cambridge University Press, 1990)
The original edition of Kant: Political Writings was first published in 1970, and has long been established as the principal English-language edition of this important body of writing. In this new, expanded edition, two important texts illustrating Kants's view of history are included for the first time: his reviews of Herder's Ideas on the Philosophy of The History of Mankind and Conjectures on the Beginning of Human History; as well as the essay What is Orientation in Thinking. In addition to a general introduction assessing Kant's political thought in terms of his fundamental principles of politics, this edition also contains such useful student aids as notes on the texts, a comprehensive bibliography, and a new postscript, looking at some of the principal issues in Kantian scholarship that have arisen since first publication.
Title from publisher's bibliographic system (viewed on 13 May 2019).
Keywords: elektronické knihy; electronic books; Political science -- Early works to 1800.